Chapter Grain size, nutrients and heavy metals analysis to evaluate natural vs anthropogenic sources in the sea environment (Naples Bay, Eastern Tyrrhenian Sea) - MILIA, ALFONSA (Monitoring of Mediterranean Coastal Areas: Problems and Measurement Techniques, 2022)
Naples Bay is affected by metal contamination of geogenic and anthropogenic nature. The grain size, organic matter, nutrients, and metal content of the seafloor sediments were analysed through a statistical approach, and a comparison was made with data ashore. The results identified four zones: one contaminated by volcanic rocks; a second and third zone contaminated by anthropogenic inputs; and a fourth distal zone with a low contamination rate. The results show that the river should be considered as a major source of anthropogenic contamination.